2012
DOI: 10.2147/vhrm.s28652
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death in eating disorders

Abstract: Eating disorders are usually associated with an increased risk of premature death with a wide range of rates and causes of mortality. “Sudden death” has been defined as the abrupt and unexpected occurrence of fatality for which no satisfactory explanation of the cause can be ascertained. In many cases of sudden death, autopsies do not clarify the main cause. Cardiovascular complications are usually involved in these deaths. The purpose of this review was to report an update of the existing literature data on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…In AN, the neuroendocrine alterations are also accompanied by autonomic dysfunctions like lower blood pressure values, lack of circadian variation of blood pressure and bradycardia (Oswiecimska et al, 2007). Thus, ghrelin might participate in AN to the cardiovascular complications observed in AN (Casiero and Frishman, 2006; Jáuregui-Garrido and Jáuregui-Lobera, 2012), but no studies currently display any correlation between these cardiovascular risks and the high plasma levels of ghrelin.…”
Section: Ghrelin a Key Energy Balance Hormone: Role In Anorexia Nervosamentioning
confidence: 99%
“…In AN, the neuroendocrine alterations are also accompanied by autonomic dysfunctions like lower blood pressure values, lack of circadian variation of blood pressure and bradycardia (Oswiecimska et al, 2007). Thus, ghrelin might participate in AN to the cardiovascular complications observed in AN (Casiero and Frishman, 2006; Jáuregui-Garrido and Jáuregui-Lobera, 2012), but no studies currently display any correlation between these cardiovascular risks and the high plasma levels of ghrelin.…”
Section: Ghrelin a Key Energy Balance Hormone: Role In Anorexia Nervosamentioning
confidence: 99%
“…Sudden cardiac death is a leading cause of premature death among eating disorder patients (Jáuregui-Garrido & Jáuregui-Lobera, 2012). A reliable marker is necessary in order to identify at-risk patients and prevent subsequent adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Eating disorders are associated with serious medical complications and premature death from a myriad of causes (Jáuregui-Garrido & Jáuregui-Lobera, 2012). A high percent of premature deaths are linked to adverse cardiovascular events, including cardiac arrhythmias which precipitate sudden cardiac death (Jáuregui-Garrido & Jáuregui-Lobera, 2012;Takimoto, Yoshiuchi, & Akabayashi, 2008). Predicting adverse cardiac events in this population is difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No suicide cases were identified in our study, which was probably because the population included inpatients only. Few studies have suggested the possibility of sepsis-induced death in ED patients [16,17]. Furthermore, a previous review indicated that IVH was not associated with an increase in sepsis compared with EN [18].…”
Section: Discussionmentioning
confidence: 99%